Characteristics of ciprofloxacin-resistant Enterobacteriaceae isolates recovered from wastewater of an Algerian hospital - Lynda Anssour; Yamina Messai; Vanesa Estepa; Carmen Torres; Rabah Bakour (Journal of Infection in Developing Countries)
Introduction: Hospital effluents are a source of environmental pollution by drugs, antibiotic-resistant bacteria, and resistance genes. Quinolones, particularly ciprofloxacin, are commonly detected in these effluents, contributing to the emergence of antimicrobial resistance. The objective of this study was to characterize ciprofloxacin-resistant Enterobacteriaceae in hospital effluents. Methodology: Isolates were selected on Tergitol-7 agar supplemented with ciprofloxacin and genotyped by ERIC-PCR. Antibiotic susceptibility testing was done using the disk diffusion method, and minimum inhibitory concentrations were determined using the agar dilution method. Resistance genes, integrons, phylogenetic groups, and sequence types were identified by PCR and sequencing. Results: A total of 17 ciprofloxacin-resistant isolates were characterized: Escherichia coli, Escherichia vulneris, Klebsiella pneumoniae, Klebsiella oxytoca, Citrobacter freundii, and Citrobacter koseri/farmeri. Isolates presented concomitant resistance to nalidixic acid, ciprofloxacin, ofloxacin, and pefloxacin. A diversity in mutation patterns in gyrA and parC genes and new amino-acid substitutions in GyrA subunit were observed. Quinolone plasmidic resistance genes qnrB1, qnrB2, qnrB5/19, qnrS1, and aac(6’)-Ib-cr were detected. Resistance to other antibiotic classes was observed. Class 1 integrons and resistance genes blaCTX-M-15, blaOXA-1, sul1, sul2, sul3, tetA, tetB, aadA1/2, aadA5, aph(3’)-Ia, aac(3)II, dfrA1, dfrA5, dfrA7, and dfrA12 were detected. Bacterial tolerance to cadmium, zinc, and mercury was observed with the presence of the merA gene. E. coli isolates belonged to phylogenetic groups A, B1, and D and to sequence types ST405, ST443, ST101, ST10, and ST347. Conclusions: This study highlighted bacterial multidrug resistance linked to ciprofloxacin and, consequently, the risk of bacterial exposure to this antibiotic.